Exploratory Research to Create a Dynamic Framework for Strategic Style (International Journal of Management and Sustainability, 2019)
Enterprises can employ various strategic styles. These include specialization, vertical integration, diversification, and internationalization. At present, there is no general dynamic framework for strategic style which could be used by entrepreneurs during a period of diversification. Different strategic styles obtained from a review of the literature enable the researcher to formulate the optimum combination of styles necessary to building a complete dynamic framework for entrepreneurs. Based on the two directions of localization and internationalization, this study established a strategic rationalized and scientific framework. In addition, to improve the reliability and stability of the enterprise, the framework has been formulated to manage and ameliorate risk during the different stages. Based on an empirical investigation, the study evaluates the results achieved by enterprises that adopted the most appropriate strategic style. Thus, the researcher intends to provide correct strategic framework through which enterprises may diversify successfully. A qualitative method is used throughout.